Kolaborasi Pemerintah Desa dan Akademisi dalam Membangun Kesadaran Branding Digital bagi Pelaku UMKM Desa - Dian Nurvita Sari; Romdoni, Firman; Farisal, Umar; Rohmatunisa, Raden Nita (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Digitalization has become an essential strategy for micro, small, and medium enterprises (MSMEs) to strengthen competitiveness in an increasingly connected marketplace. This study examines the role of digital branding in enhancing the visibility and market reach of UMKM in Desa Mekarsari and Desa Sukatani, Rajeg District, Tangerang Regency, through collaboration between local government and academia. The research aims to identify current branding awareness levels among UMKM actors, explore the implementation of digital branding strategies, and provide recommendations for improvement. Using a qualitative descriptive method, data were collected through interviews, field observations, and literature review. The findings reveal that although UMKM actors have recognized the importance of digital branding, their application of effective strategies remains limited due to constraints in digital literacy, resources, and platform optimization. The study concludes that strengthening capacity-building programs, optimizing the use of social media and e-commerce, and fostering sustainable collaboration between stakeholders are crucial to maximizing the impact of digital branding on UMKM growth.